(untitled) (Journal of the College of Basic Education, 2025)
The research aims to prepare educational units according to the strategy of organizing the learning of skills in motor flexibility and learning the forehand serve in table tennis. The researcher used the experimental method to achieve the study objectives and contribute to solving the research problem. The original research community was determined using the intentional method, as well as the research community. The sample was selected randomly using a lottery method and represented middle school students, numbering (28) students, who were divided into two groups, each group (14) students. The researcher concluded the positive effect of the strategy of organizing the learning of skills on motor flexibility and learning the skill of the forehand serve with the face of the racket. As for the recommendations, it is necessary to benefit from the strategy of organizing in learning the skill of the table tennis serve.